1987
DOI: 10.1097/00006842-198709000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of major depression in renal dialysis patients.

Abstract: Controversy exists regarding the frequency of depression in renal dialysis patients. We have assessed an unselected sample of 99 dialysis patients using the Diagnostic Interview Schedule (DIS). A current Major Depressive Episode (MDE) was diagnosed in 8.1% of the sample, one-half of whom had a past history of MDE. An additional 12.1% had only a past history of depression. In contrast to patients with no affective disorder, characteristics of patients with a current MDE included the following: a history of prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
2
11

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 34 publications
(31 reference statements)
3
46
2
11
Order By: Relevance
“…Association of depressed mood with unemployment among dialysis patients was reported Ͼ20 years ago by Craven et al (5), who assessed patients for major depressive episode using the Diagnostic Interview Schedule. Researchers who used the Beck Depression Inventory and the Hospital Anxiety and Depression Scale (6,7) also found an association of depressed mood with unemployment among dialysis patients, and Finkelstein et al (15) noted that depressive affect (pessimism, anhedonia, sadness, complaints of feeling helpless and hopeless) may contribute to reduced occupational activity.…”
Section: Discussionmentioning
confidence: 95%
“…Association of depressed mood with unemployment among dialysis patients was reported Ͼ20 years ago by Craven et al (5), who assessed patients for major depressive episode using the Diagnostic Interview Schedule. Researchers who used the Beck Depression Inventory and the Hospital Anxiety and Depression Scale (6,7) also found an association of depressed mood with unemployment among dialysis patients, and Finkelstein et al (15) noted that depressive affect (pessimism, anhedonia, sadness, complaints of feeling helpless and hopeless) may contribute to reduced occupational activity.…”
Section: Discussionmentioning
confidence: 95%
“…In a study, it was reported that according to Beck Depression Inventory, 47% of the patients with ESRD have a score above the cutoff point, but major depression is diagnosed in only 5% of them as a result of structured interviews (32). In ESDR, somatic symptoms such as lack of appetite, sleep disorders, fatigue, and lack of energy, which were also reported frequently in psychiatric disorders, were commonly encountered as a result of the disease and hemodialysis, so it became particularly important to assess patients with ESRD with structured interviews (34).…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com nossos resultados, o tempo em programa de diálise foi preditivo de melhor adaptação ao tratamento e mostrou consistência com dados da literatura, como o estudo de Craven et al (1987), que demonstrou maior prevalência de depressão em 99 indivíduos nos primeiros dois anos do tratamento. Pacientes com IRC freqüentemente experimentam melhora nas condições médicas após o início da diálise e necessitam de algum tempo para se adaptar à nova situação, demonstrando acostumar-se ao tratamento após tempo médio de um ano (Craven et al, 1987).…”
Section: Figura 1 Prevalência Dos Transtornos Psiquiátricos Encontraunclassified
“…Pacientes com IRC freqüentemente experimentam melhora nas condições médicas após o início da diálise e necessitam de algum tempo para se adaptar à nova situação, demonstrando acostumar-se ao tratamento após tempo médio de um ano (Craven et al, 1987).…”
Section: Figura 1 Prevalência Dos Transtornos Psiquiátricos Encontraunclassified